Videoclipe para aprendizagem da fisiologia da lactação: avaliação da usabilidade por profissionais da saúde na atenção hospitalar - Freitas, Eva Inês Vilanova Ribeiro (2023)
Introduction: The breastfeeding rate is below the recommended level, which is why health promotion is essential for professionals and women to understand how lactation occurs and make informed decisions. One of the important topics is the physiology of lactation because the interaction of hormones and the stimulation of sucking and milking can affect the beginning and continuous production of milk. Understanding this can even combat the belief of insufficient milk and its consequences. The physiology of lactation is a complex and abstract subject, and educational technologies can enhance learning. General objective: To evaluate the usability of a video clip for learning the physiology of lactation by maternal and neonatal health professionals and identify the barriers and facilitators for the use of the video clip in the hospital context. Method: Cross-sectional study guided by the Knowledge Translation to Action Model. It was conducted with 63 healthcare professionals from the Obstetric Center, Joint Lodging, and Neonatal Intensive Care Unit of the University Hospital of Santa Maria, Rio Grande do Sul, Brazil. The self-administered electronic form consisted of the System Usability Scale (SUS) instrument and open-ended questions about barriers and facilitators for the use of the video clip, available at http://ntetube.nte.ufsm.br/v/1617720387. Spearman's correlation test was used to evaluate the correlation between quantitative variables. A significance level of 5% was considered for the established comparisons. Cronbach's alpha was 0.78, indicating the reliability of the instrument in this population. Results: The professionals evaluated the usability of the video clip as the best imaginable (median 95), which was positively associated with longer training time (p = 0.038) and motivation for the use of technology (p = 0.035). Healthcare professionals indicated that they have expectations (92.1%), motivation (88.9%), knowledge (95.2%), and ability (92.1%) to use the video clip. Facilitators for use included having an institutional training schedule, physical space in the unit for educational activities, moments of breastfeeding guidance and a brief video clip with easy and playful information. Barriers included overcrowding and turnover, lack of audiovisual equipment, limited internet access, need for human resources in units, and difficulty in developing group activities. Conclusion: The evaluation of healthcare professionals regarding the video clip for learning the physiology of lactation indicates the potential usability of this tool in maternal and neonatal care hospital units. There is a need to minimize barriers in physical infrastructure and human resources in the local context.